Pengaruh Kepemimpinan dan Motivasi terhadap Disiplin Kerja Serta Dampaknya pada Kinerja Karyawan Studi Pada PO. Sumber Alam - Daru Amanta Rahmadani; E. Didik Subiyanto; Epsilandri Septyarini (Universitas Batanghari, 2023)
This study aims to determine the effect of Leadership and Motivation on Work Discipline and their impact on Employee Performance at PO. Purworejo Natural Resources. This research method uses descriptive quantitative and primary data using a questionnaire. The population in this study were employees (driver, mechanic, counter clerk) PO. Natural Resources totaling 60 people. The sampling technique in this study is non-probability sampling. Data was obtained by distributing a list of questionnaire questions to 60 respondents. The data source of this research is primary data. Test the quality of the data using the Validity Test, Reliability Test, and Classical Assumption Test. The data analysis technique in this study uses Path Analysis. The results showed that Leadership and Motivation had a positive and significant effect on Work Discipline; Leadership has a negative and insignificant effect on employee performance; Motivation and Work Discipline have a positive and significant effect on Employee Performance; indirectly mediated by Work Discipline, Leadership has a positive and significant effect on Employee Performance; indirectly mediated by work discipline, motivation has a positive but not significant effect on employee performance.